Pengaruh Group Cognitive Behavior Therapy (GCBT) Terhadap Perubahan Perilaku Remaja Berisiko Penyalahgunaan NAPZA Berdasarkan StatusTempat Tinggal di Kabupaten Dharmasraya Tahun 2019 - Wisdia Lola Erwinda; Susmiati Susmiati; Heppi Sasmita (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Background: Dharmasraya District is very prone and vulnerable to drug circulation cases because Dharmasraya district consists of various ethnic and is a cross-Sumatran crossing area so it is necessary to prevent the behavior of abuse NAPZA on adolescent. Purpose: This study aimed to determine the influence of the Group Cognitive Behaviour Therapy (GCBT) on the change of adolescent behaviour at risk of drugs based on residential status in Dharmasraya District in 2019. Method: The design of this research is the Quasi experiment of PreTest PostTest With Control Group by the amounts of samples 64 consisting of 32 control groups and 32 intervention groups. Results: Research on the intervension group and adolescent living with parents showed significant influence on adolescent behaviour changes. Whereas in the control group and adolescent who do not live with parents showed no significant influence on adolescent behaviour changes Conclusion: Group Cognitive Behavior Therapy can be used to change adolescent behavior at risk of drugs abuse and Hopefully the implementation of cognitive behaviour therapy can be applied at schools in cooperation with health service and parents to prevent risky behaviour.